2012
DOI: 10.1111/cfs.12049
|View full text |Cite
|
Sign up to set email alerts
|

Family group conferences: evidence, outcomes and future research

Abstract: A B S T RA C TThis is the second article of a two-part review of the literature relating to family group conferences (FGCs); it explores outcomes and challenges in implementing FGCs. The complex data relating to outcomes, drawing on a range of national contexts, is presented. The challenges of researching outcomes and the role of longitudinal and randomized, controlled trials are considered. The article concludes with a discussion of the implementation of FGC policy and practice in the contemporary context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…These approaches include family group conferences (Clarijs & Malmberg, 2012;Burford & Hudson & 2000). Research on the implementation of family group conferences showed that the key to success is investing in the social networking of families (Frost, Abram & Burgess, 2014). To support the thirdlevel services we should have and use tools to promote relations between the recipients of services (children and their parents) and the institutions providing services (social service authorities, courts, and police).…”
Section: Resultsmentioning
confidence: 99%
“…These approaches include family group conferences (Clarijs & Malmberg, 2012;Burford & Hudson & 2000). Research on the implementation of family group conferences showed that the key to success is investing in the social networking of families (Frost, Abram & Burgess, 2014). To support the thirdlevel services we should have and use tools to promote relations between the recipients of services (children and their parents) and the institutions providing services (social service authorities, courts, and police).…”
Section: Resultsmentioning
confidence: 99%
“…Empirical literature regarding the study of outcomes of FGC has been critiqued for being methodologically weak (Crampton, 2007;Frost, Abram, & Burgess, 2014). Isolating the effects of FGC from the influence of other services that are typically offered alongside FGC appears difficult to assess (Crampton, 2007).…”
Section: Family Group Conferencingmentioning
confidence: 99%
“…Family group conferencing (FGC) has generated interest as a decision‐making model for child protection (see amongst others Brown ; Connolly , ; Frost et al . , ; Healy & Darlington ; Healy et al . ; Holland & O'Neill ; Morris & Connolly ; Ney et al .…”
Section: Introductionmentioning
confidence: 99%
“…Family group conferencing (FGC) has generated interest as a decision-making model for child protection (see amongst others Brown 2003;Connolly 2006aConnolly , 2006bFrost et al 2014aFrost et al , 2014bHealy & Darlington 2009;Healy et al 2012;Holland & O'Neill 2006;Morris & Connolly 2012;Ney et al 2013;Wang et al 2012;Weigensberg et al 2008). According to these authors, FGC engenders stronger family involvement and collective responsibility and therefore generates more safety than traditional methods in youth care.…”
Section: Introductionmentioning
confidence: 99%